Phagocyte function and cytokine production in community acquired pneumonia. Issue 2 (February 1994) - Moussa, K; Michie, H J; Cree, I A; McCafferty, A C; Winter, J H; Dhillon, D P; Stephens, S; Brown, R A
Abstract : BACKGROUND--It is possible that many deaths from pneumonia may involve the generation of inflammatory mediators and tissue damage by activated phagocytes. To test this hypothesis phagocyte function, plasma levels of interleukin 6 (IL-6), tumour necrosis factor alpha (TNF alpha), and soluble interleukin 2 receptor (IL-2R), disease severity, and outcome have been examined in 46 patients with community acquired pneumonia. METHODS--Polymorphonuclear leucocyte (PMNL) and monocyte function were measured daily by chemiluminescence in these patients during the first week of admission, and cytokine levels were subsequently determined by ELISA. A series of 61 healthy individuals were used as a control group for the chemiluminescence results. RESULTS--There was evidence of phagocyte, particularly PMNL, activation on admission in 76% of the patients. Most patients (86%) also had raised IL-2R levels on admission. IL-6 and unbound TNF alpha were present in 23% and 41% of patients at varying times during the course of the disease. There was little correlation between measurements of cytokine or phagocyte levels and outcome or indicators of disease severity, although this may be because of the small number of patients included in this preliminary study. CONCLUSIONS--These results are consistent with the hypothesis that activated phagocyte function and raised levels of circulating cytokines may contribute to the pathogenesis of community acquired pneumonia. There are striking similarities in this respect between pneumonia, adult respiratory distress syndrome, and sepsis.